ANALISIS KINERJA WATER COOLED CHILLER MENGGUNAKAN FLUIDA R-134A PADA GEDUNG X - Yolanda Siahaan, (2023)
Indonesia as a country with a tropical climate, is in dire need of an air conditioning system that is useful for creating thermal comfort for occupants and the production process of industrial equipment in a building, using a different method, namely cold water as the source. The HVAC system is a cooling system that is used to control temperature, humidity and air pressure to be lower than the ambient temperature to achieve the desired conditions. Water cooled chiller is a refrigeration machine that uses cold water as an indirect cooling system. The first step in planning the HVAC system is to calculate the cooling load in the building's room to find out whether the capacity of the chiller cooling system can handle the cooling load or not. In this study, the calculation of the cooling load using the CLTD (Cooling Load Temperature Difference) method. From the results of calculating the cooling load in building X, it shows an average total cooling load of 10.312.346,16 Btu/hr which is mostly generated from the internal load of the equipment, with a chiller capacity of 6.002.981,42 Btu/hr, and with the performance of the water cooled chiller in efficient conditions with an average COP value of 9,09.